1991
DOI: 10.1007/bf00179715
|View full text |Cite
|
Sign up to set email alerts
|

Discoid lateral meniscus

Abstract: Discoid meniscus is uncommon and usually affects the lateral meniscus. We present 16 patients (8 male and 6 female) with tears of a discoid lateral meniscus occurring in 1800 arthroscopies. We carried out an arthroscopic partial meniscectomy leaving an intact peripheral rim. This is biomechanically satisfactory and the early results are encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…2,3,7 Because the discoid meniscus has anomalous morphology and an awkward position, it is easy to cause tears and degenerative changes. 13,23 The distribution of the tear pattern has been reported in a number of studies. Hayashi et al 10 reported that the longitudinal tear is the most common type of discoid meniscus damage.…”
Section: Discussionmentioning
confidence: 98%
“…2,3,7 Because the discoid meniscus has anomalous morphology and an awkward position, it is easy to cause tears and degenerative changes. 13,23 The distribution of the tear pattern has been reported in a number of studies. Hayashi et al 10 reported that the longitudinal tear is the most common type of discoid meniscus damage.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, superiority of the long‐term knee functionality after arthroscopic central partial meniscectomy–saucerization of intact DLM in comparison with that regarding the torn DLM was demonstrated. These findings in combination with the fact of the high tear rate observed among discoid menisci [16, 20, 23, 38, 44], probably attributable to altered biomechanics and distortion of the collagen matrix, may raise a concern regarding the management of an intact discoid meniscus encountered incidentally during arthroscopic investigation. Current trend suggests that no treatment is required for the asymptomatic discoid meniscus [5].…”
Section: Discussionmentioning
confidence: 99%
“…14 Current treatment recommendations favor partial resection (saucerization) to a stable peripheral rim for symptomatic complete and incomplete discoid meniscal tears. 2,4,5,7,11 When peripheral longitudinal vertical tears are present, meniscal repair techniques may be used. Ikeuchi 7 described three patients with peripheral tears treated with central saucerization and peripheral rim repair.…”
Section: Case Reportmentioning
confidence: 99%
“…A discoid meniscus is a congenital variant that involves the lateral meniscus more frequently than the medial. The incidence of this variant in several clinical studies ranges from 0.4% to 17%, 1,5,7 while the incidence in a large cadaver study was 5%. 2 The most common symptoms of discoid meniscus are pain, locking, and a snapping sound, 9 and these symptoms can occur with both intact and torn discoid menisci.…”
mentioning
confidence: 92%